Accelerating Digital Connectivity Through Infrastructure Sharing - Strusani, Davide; Houngbonon, Georges V. (International Finance Corporation, Washington, DC, 2020)
Digital connectivity has enormous potential to support development. Yet today some four billion people in emerging economies remain offline, partly due to a lack of affordable Internet access. Sharing infrastructure among operators and across sectors is a potential solution. It can accelerate digital connectivity at lower cost, especially in the least developed markets where returns to investment can be limited. It can also reduce investment costs and operating expenses for investors and operators and increase their balance sheet sustainability. Sharing models can also benefit consumers by increasing competition, lowering prices, and raising service quality. The private sector has already embraced this model; further expansion requires targeted policies that promote competition and facilitate sharing.